2011
DOI: 10.2139/ssrn.1857488
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Versus Deep Integration Between Mediterranean Countries and the EU and Within the Mediterranean Region

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…The potential for trade expansion between the EU and the MED-11 as well as among the MED-11 countries that could result from lowering tariffs, and easing non-tariff barriers -including improving trade logistics -is discussed in Ghoneim et al (2012). 32 De Wulf &Maliszewska (2009) provide details on how the EU could help in this deepening of economic integration between the EU and MED-11 with well-targeted support initiatives that should go beyond the lowering of tariffs that was the main approach of the Association Agreements.…”
Section: Resultsmentioning
confidence: 99%
“…The potential for trade expansion between the EU and the MED-11 as well as among the MED-11 countries that could result from lowering tariffs, and easing non-tariff barriers -including improving trade logistics -is discussed in Ghoneim et al (2012). 32 De Wulf &Maliszewska (2009) provide details on how the EU could help in this deepening of economic integration between the EU and MED-11 with well-targeted support initiatives that should go beyond the lowering of tariffs that was the main approach of the Association Agreements.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have, mostly indirectly, assessed the role of NTMs in MENA countries. For example, it has been argued that NTMs have played an important role in explaining the low intra-regional trade of the region (Ghoneim et al, 2011) whether the main reasons have been economic, political, or institutional. Interestingly, when tariffs jei Middle East and North African Integration: through the lens of Non-Tariff Measures were reduced due to multilateral commitments or the full implementation of regional agreements, the use of NTMs started to gain momentum as a device to impede trade while acting as a substitute to the high tariffs and traditional NTMs (e.g.…”
Section: A Role Of Ntms In Mena Countriesmentioning
confidence: 99%
“…Other studies (Konan, 2003;Abedini and Péridy, 2008;Ghoneim et al, 2011) focused on the expected benefits of deepening trade among Arab countries. In fact, such studies identified that deep integration among Arab countries (e.g.…”
Section: A Role Of Ntms In Mena Countriesmentioning
confidence: 99%
“…To estimate the trade creation effects of shallow and deep integration, Ghonheim et al (2011) observed that it is important that all the relevant policy measures be considered as a package and not independently as the effects are not additive.…”
Section: Infrastructure Investment and International Tradementioning
confidence: 99%